Reliability of Moral Distress Scale, Secondary Traumatic Stress Scale, and Jefferson Scale of Empathy Among Greek Nurses: A Pilot Study - Gamvrouli, Maria; Karanikola, Maria; Paschali, Antonia; Giannakopoulou, Margarita (My University, 2024)
Background and Purpose: Moral distress (MD), secondary traumatic stress (STS), and empathy are of particular interest to the nursing profession. The availability of validated tools for the assessment of these parameters is of high importance. The primary aim of this pilot study was to evaluate the reliability of the Greek version of the MD Scale or the revised version (MDS-R), the Jefferson Scale of Empathy for Health Professionals (JSE-HP), and the STS Scale (STSS) in Greek nurses working in open and psychiatric wards. Methods: To assess the reliability of scales, internal consistency (coefficient alphas) and test-retest (interclass correlation coefficients [ICCs]) were calculated. Results: A total of 38 nurses took part in the study. All scales and subscales presented excellent stability (.876 ≤ ICC ≤ .963, p < .0001) and acceptable to excellent internal consistency reliability (first measurement, .796 ≤ coefficient alpha ≤ .959; second measurement, .794 ≤ coefficient alpha ≤ .956). Conclusions: The Greek version of MDS-R, STSS, and JSE-HP may be proposed for the assessment of relevant variables in Greek nursing staff.
Keywords: test-retest reliability; empathy; internal consistency; moral distress; nursing staff; secondary traumatic stress